Three hours of intermittent hypoxia increases circulating glucose levels in healthy adults. Issue 1 (13th January 2017) - Newhouse, Lauren P.; Joyner, Michael J.; Curry, Timothy B.; Laurenti, Marcello C.; Man, Chiara Dalla; Cobelli, Claudio; Vella, Adrian; Limberg, Jacqueline K.
Abstract: An independent association exists between sleep apnea and diabetes. Animal models suggest exposure to intermittent hypoxia, a consequence of sleep apnea, results in altered glucose metabolism and fasting hyperglycemia. However, it is unknown if acute exposure to intermittent hypoxia increases glucose concentrations in nondiabetic humans. We hypothesized plasma glucose would be increased from baseline following 3 h of intermittent hypoxia in healthy humans independent of any effect on insulin sensitivity. Eight (7M/1F, 21–34 years) healthy subjects completed two study visits randomized to 3 h of intermittent hypoxia or continuous normoxia, followed by an oral glucose tolerance test. Intermittent hypoxia consisted of 25 hypoxic events per hour where oxygen saturation (SpO2 ) was significantly reduced (Normoxia: 97 ± 1%, Hypoxia: 90 ± 2%, P  < 0.01). Venous plasma glucose concentrations were measured on both visits before and after the 3 h protocol. No changes in plasma glucose were observed from baseline after 3 h of continuous normoxia (5.1 ± 0.2 vs. 5.1 ± 0.1 mmol/L, P  > 0.05). In contrast, circulating glucose concentrations were increased after 3 h of intermittent hypoxia when compared to baseline (5.0 ± 0.2 vs. 5.3 ± 0.2 mmol/L, P  = 0.01). There were no detectable changes in insulin sensitivity following intermittent hypoxia when compared to continuous normoxia, as assessed by the oral glucose tolerance test ( P  > 0.05). Circulating glucose is increased after 3 h of intermittent hypoxia in healthy humans, independent of any lasting changes in insulin sensitivity. These novel findings could explain, in part, the high prevalence of diabetes in patients with sleep apnea and warrant future studies to identify underlying mechanisms. Abstract : Circulating glucose is increased after 3 h of intermittent hypoxia in healthy humans, independent of any lasting changes in insulin sensitivity. These novel findings could explain, in part, the high prevalence of diabetes in patients with sleep apnea and warrant future studies to identify underlying mechanisms.